(untitled) (REMUNOM, 2024)
The use of organic fertilizers has increasingly gained traction as a sustainable and accessible alternative for agriculture, especially in Brazil, where food and grain production is so important. In this text, we will explore the role of organic fertilizers, with a focus on practices such as composting and bioconversion using black soldier fly larvae (Hermetia illucens). These practices not only help improve soil fertility and health but also address the issue of organic waste, strengthening more sustainable agriculture. By revisiting the history of natural fertilizers and recent advancements, we can see how organic fertilizers have the potential to transform agriculture and drive a global shift towards regenerative practices, which aim to restore and maintain soil health, creating a more balanced and productive cycle.